Religious Education and the Delegitimation of Knowledge - Seyed Mahdi Sajjadi (International Institute of Islamic Thought, 2008)
The velocity of information production has increased at all levels, including the global. These expansions lead to the delegitimation of knowledge by equating information with knowledge or the predominance of information over knowledge. Given that this situation has caused epistemological challenges for the process of religious education, this article attempts to study the epistemological problems and challenges posed by information technology (IT) in this area.